Structure characterization of Grifola frondosa polysaccharide and its effect on insulin resistance in HFD-fed mice - Yin-Yi Ding; Jinchi Lan; Yuxin Wang; Yuxiang Pan; Tianyuan Song; Shizhu Liu; Zhenyu Gu; Yujun Ge (npj Science of Food)
Abstract Polysaccharide extracted from Grifola frondosa (GFP) was selected in this study. After preliminary separation, four factions were collected, named GFP-F1, GFP-F2, GFP-F3 and GFP-F4. GPF-F2 was further separated into two fractions, namely GFP-N1 and GFP-N2. The molecular weight of GFP-N1 and GFP-N2 was 3.323×103 kDa and 10.8 kDa, respectively. GFP-N1 was composed of glucose and galactose and 1 → 3, 1 → 4, and 1 → 6 glycosidic bonds. GFP-N2 was composed of glucose, galactose and mannose and 1 → 2, 1 → 3, 1 → 4, and 1 → 6 glycosidic bonds. GFP could significantly relieve the insulin resistance induced by HFD. GFP significantly alleviated gut microbiota disturbance caused by HFD and increased the production of short-chain fatty acids, and further reduced the expression of LPS/TLR4 inflammatory pathway. GFP significantly reduced the oxidative stress induced by HFD, increased the expression of the Nrf2/ARE signaling pathway. These results indicated that GFP could be developed as a potential ingredient for the management of insulin resistance.